Milking technique and other factors affecting milk production potential in different breeds of camels under farm conditions - Sahani, M S; Rathinasabapathy, M; Gorakhmal, Gorakhmal; Khanna, N D (The Indian Journal of Animal Sciences, 2012)
Daily milk production in 4 lactating camels each of Bikaneri and Kachchhi breed belonging to second and third parities and 3lactating camels of Jaisalmeri breed from third parity was studied. The daily milk production was recorded twice a day at12-hr interval by 3 different milking techniques, viz. 2-teat stripping and allowing calf to suckle simultaneously, 4-teatstripping, and machine milking. The average daily productions by 2-teat and 4-teat stripping, and machine milking in Bikanericamels were 4.19±0.11, 3.2±0.15 and 2.66±0.16kg/day respectively. The corresponding figures in Jaisalmeri were 3.72± 0.17,2.17±0.16 and 2.02±0.19 kg/day, respectively. The average daily productions in Kachchhi camels with 4-teat stripping andmachine milking was 3.94±0.13 and 3.42±0.14 kg respectively. The morning, evening and total daily production per day werehigher under 2-teat stripping followed by 4-teat stripping and machine milking. The contribution of breed and parity wassignificant (P<0.01) under all the 3 milking techniques. The daily milk production with 2-teat stripping varied from2.37±0.27 to 6.73±0.27 kg/day, with 4-teat from 0.66±0.26 to 5. 15±0.25 kg/day and with machine 1.45±0.23 to 5.22±0.04kg/day. The daily milk production was highest during month 6 of lactation and then it started declining. The month-wise dailyaverage of second parity females varied from 1.61±0.31 to 4.64±0.31 kg/day and for third parity from 2.13±0.25 to 5.86±0.25kg respectively. The contribution of parity on month of lactation was significant (P<0.1). As compared to evening, themorning milk yield was about 10.0 to 27.0% higher during different months of lactation. The chemical composition of milkduring early and late phases of lactation indicated that pH, fat %, SNF and total solids were significantly higher duringlate phase of lactation. However, the proteins were also higher but not at significance level. Vitamin C was higher at earlyphase of lactation.